Investing decisions and life satisfaction for the elderly investors - Adrian-Gabriel Enescu; Monica Răileanu Szeles (Cogent Economics & Finance)
Our paper examines the impact of investment choices on life satisfaction among elderly investors, using longitudinal data from waves 4-8 of the Survey of Health, Ageing and Retirement in Europe (SHARE). We applied a two-stage regression approach: first, a logit regression to address endogeneity with an instrumental variable, followed by ordered logit regressions. Countries were grouped based on economic conditions. The results illustrate that aggressive investing is a significant predictor of life satisfaction among elderly investors in less developed countries. Furthermore, the positive impact of aggressive investing among elderly investors is maintained robust after replacing the response variable with the positive outlook on life for both groups of countries. Mediation analysis suggests that life meaning mediates the link between aggressive investing and life satisfaction, with investment behavior potentially providing elderly individuals with a sense of purpose. Another finding of our paper is that investors from less developed European countries reported higher life satisfaction than non-investors while controlling for other factors that may influence the relationship. We have formulated policy recommendations aimed at increasing the life satisfaction of the elderly.